Case series of COVID-19 in chronic kidney disease patients under peritoneal dialysis at a northern Portuguese center - Silva,Rui F. (2022)
ABSTRACT COVID-19 is a pandemic and life-threatening respiratory disease. Chronic kidney disease is a probable risk factor for more severe COVID-19, but outcomes in the peritoneal dialysis population are scarce. We analyzed our peritoneal dialysis center COVID-19 cases from March 2020 to January 2021, before full vaccination with the Pfizer BNT 162b2 mRNA vaccine in February 2021. There were 13 cases of COVID-19 out of 96 patients on peritoneal dialysis (cumulative incidence 13,5 cases per 1000 patients-month). Nine were considered mild (76,9%), two moderate (15,4%) and one severe/critical (7,7%). There was one asymptomatic case. The most common presenting signs and symptoms were myalgia, cough, fever, asthenia, hypotension, and loss of smell and/or taste. Only one patient required oxygen in the ICU. There was a hospitalization rate of 30,8% (three mild and one severe/critical) and a median time of hospitalization until discharge, or death, of 6 days. The most common reason for hospitalization was hypotension and asthenia, without respiratory failure (three mild out of four hospitalizations). One patient died (7,7%) and 12 patients recovered well (92,3%). Of eleven patients presenting with COVID-19 symptoms, nine reported persisting symptoms for over one month (81,8%). In conclusion, COVID-19 in patients under peritoneal dialysis had a relatively benign course with symptoms mainly unrelated to the respiratory tract.